2016
DOI: 10.4238/gmr.15028226
|View full text |Cite
|
Sign up to set email alerts
|

A network approach predicts NFKBIA and BIRC3 as pathogenic genes in childhood asthma

Abstract: ABSTRACT. This study aimed to predict pathogenic genes of childhood asthma based on molecular interaction networks and gene expression data. Known pathogenic genes identified from the human protein-protein interaction network were denoted as seed genes, and were included in network A. We extracted sub-network B (pathogenic network), which consisted of genes that interacted with at least two seed genes. We assigned a weight to select the pathogenic genes from this network according to its interactions and co-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was reported that BIRC3 was upregulated in asthma [ 22 , 23 ] and was predicted as a pathogenic gene involved in childhood asthma [ 24 ]. Similarly, we found that BIRC3 mRNA and protein were significantly upregulated in asthma, and the results of AUC demonstrated its good diagnostic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that BIRC3 was upregulated in asthma [ 22 , 23 ] and was predicted as a pathogenic gene involved in childhood asthma [ 24 ]. Similarly, we found that BIRC3 mRNA and protein were significantly upregulated in asthma, and the results of AUC demonstrated its good diagnostic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, however, linked single-nucleotide polymorphisms in BIRC3, the inhibitor of apoptosis associated with the TWEAK pathway, with reduced The Journal of Immunology asthma susceptibility and reduced loads of circulating eosinophils (36). Furthermore, BIRC3 has been identified as a potential pathogenic gene in childhood asthma based on a molecular interaction network study (37).…”
Section: Discussionmentioning
confidence: 99%
“…For example, deficiency or absence of Lbp leads to increased susceptibility of mice to S. typhimurium and K. pneumoniae infections [Jack et al, 1997;Le Roy et al, 2001;Fierer et al, 2002]. On the other hand, promoter polymorphisms resulting in reduced expression of Nfkbia are associated with susceptibility to BPD and asthma [Ali et al, 2013;Gao 2016]. Reduced expression of Nfkbia is an interesting finding in light of evidence suggesting that lung phenotype of impaired alveolarization observed in fetuses generated through the transfer of both in vivo-and in vitro-derived blastocysts resembles, at least to a certain extent, to BPD [Karagenç et al, 2019;Doğan et al, 2022].…”
mentioning
confidence: 99%